2022
DOI: 10.1080/21655979.2022.2049471
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside-IV alleviates high glucose-induced ferroptosis in retinal pigment epithelial cells by disrupting the expression of miR-138-5p/Sirt1/Nrf2

Abstract: Astragaloside-IV (AS-IV) (C 41 H 68 O 14 ) is a high-purity natural product extracted from Astragalus , which has demonstrated biological activities. However, the effect of AS-IV on retinal pigment epithelial (RPE) cells in diabetic retinopathy (DR) remains unclear. In this study, high glucose (HG) was shown to promote ARPE-19 RPE cell death, increase the contents of reactive oxygen species (ROS) and oxidized glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 52 publications
1
66
0
Order By: Relevance
“…In these cells, reduced ATP production and mitochondrial membrane potential, increased ROS, accumulation of damaged, fragmented and vesiculated mitochondria, and mitophagic flux to lysosomes, were observed. NaIO 3 and high glucose have also been shown to induce RPE ferroptosis, which can be repressed by ferroptosis inhibitors (Liu et al, 2021;Tang et al, 2022). In an independent study, high glucose promoted RPE apoptosis and inhibited cell proliferation and mitophagy by inactivating ROS/Pink1/Parkin signal pathway (Zhang et al, 2019).…”
Section: Role Of Mitochondria In Retinal Pigmented Epithelial Cell Deathmentioning
confidence: 96%
“…In these cells, reduced ATP production and mitochondrial membrane potential, increased ROS, accumulation of damaged, fragmented and vesiculated mitochondria, and mitophagic flux to lysosomes, were observed. NaIO 3 and high glucose have also been shown to induce RPE ferroptosis, which can be repressed by ferroptosis inhibitors (Liu et al, 2021;Tang et al, 2022). In an independent study, high glucose promoted RPE apoptosis and inhibited cell proliferation and mitophagy by inactivating ROS/Pink1/Parkin signal pathway (Zhang et al, 2019).…”
Section: Role Of Mitochondria In Retinal Pigmented Epithelial Cell Deathmentioning
confidence: 96%
“…Ferroptosis could be triggered during development or during normal homeostatic tissue turnover, by the accumulation of (1) iron [ 25 , 26 , 27 , 28 , 29 ] or (2) PUFAs [ 17 ], or by (3) the depletion of the antioxidant glutathione (GSH) [ 30 ], decreased function of glutathione peroxidase 4 (GPX4), which mediates the reduction of lipid peroxides [ 31 , 32 ], or the activation of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase [ 33 , 34 , 35 ].…”
Section: Ferroptosis and Mechanismsmentioning
confidence: 99%
“…Similarly, the expression of miR-138–5p is upregulated in RPE cells treated with high glucose, which reduces Sirt1/Nrf2 activity and antioxidant expression and ultimately induces RPE cell ferroptosis. Astragaloside-IV alleviates high glucose-induced ferroptosis in RPE cells by disrupting the expression of miR-138–5p/Sirt1/Nrf2( Tang et al, 2022 ). In addition, a novel miR-338–3p/SLC1A5 axis has been reported that regulates oxidative stress-mediated RPE cell ferroptosis to modulate DR progression.…”
Section: Novel Regulated Cell Death In Diabetic Retinopathymentioning
confidence: 99%
“…Quercetin, resveratrol, germacrone and cryptochlorogenic acid all have been reported to have potential anti-ferroptosis properties in diabetes mellitus or its complications ( Yang and Yang, 2022 ). In a DR in vitro model, astragaloside-IV, a high-purity natural product extracted from Astragalus membranaceus, alleviates high glucose-induced ferroptosis in RPE cells by disrupting the expression of miR-138–5p/Sirt1/Nrf2( Tang et al, 2022 ). In addition, downregulation of TRIM46 increases RCEC resistance against high glucose-induced perroptosis.…”
Section: Novel Regulated Cell Death As Therapeutic Targets For Diabet...mentioning
confidence: 99%